Comparative Study Between Percutaneous Nephrolithotomy and Extra Corporeal Shock Wave Lithotripsy in Managing Renal Stones - Islam, MS; Biswas, NP; Hossan, MZ; Rahman, I; Alam, AKM K; Shameem, IA; Kibria, S; Islam, AKM A (Bangladesh Medical Journal, 2014)
To find out better treatment option in treating renal stone safely, expeditiously. A total of 90 patient were prospectively randomized for Percutaneous Nephrolithotomy (PCNL) (40) and Extra Corporeal Shock Wave Lithotripsy (ESWL) (50). Stone clearance, adjuvant procedures, hospital stay, post procedure morbidity, were compared for both methods. Stone clearance in PCNL and ESWL group was 87.50 and 66 percent respectively with a significant difference of clearance (P<0.05). Considering the stone size, in smaller stones, clearance was 87.50% and 72 50% among PCNL and ESWL group respectively without any significant difference (P>0.05). But in larger stones, stone clearance was 87.50% and 60.72% among PCNL and ESWL group respectively with significant difference in clearance between the groups (P<0.05). The rate of adjuvant procedures in PCNL and ESWL group was 12.50%, and 34% respectively. Requirement of adjuvant procedures were significantly higher in ESWL group (P<0.051 Post procedure hospital stay was significantly shorter in ESWL group than PCNL group (1.32 0.47 vs 4.52 1.99) with P yalue <0 05. Steinstrasse and Haematuria were significantly higher in ESWL group than PCNL group. Bleeding requiring transfusion, urinary cutaneous fistula and .fever were significantly higher in PCNL group than ESWL group. PCNL is more effective than ESWL in clearing larger renal stones. DOI: http://dx.doi.org/10.3329/bmj.v41i3.18954 Bangladesh Medical Journal 2012 Vol.41(3): 23-27